A kinematic-freedom analysis of a flexed-knee-stance testing rig. - Zavatsky, A (Elsevier, 1997)
The Oxford Rig was designed for biomechanical testing of post-mortem human knee-joint specimens during simulated flexed-knee stance, such as occurs when riding a bicycle, rising from a chair, or climbing stairs. It has been asserted, but never proven, that the movements of the 'ankle' and 'hip' assemblies of the Oxford Rig combine to allow a knee specimen its natural six degrees-of-freedom of movement (6 d.o.f.). This paper investigates this claim mathematically using the general mobility criterion for spatial linkages and the basics of screw theory. It is shown that within the physiological range of knee-joint movement and the physical construction of the Rig, the knee specimen is allowed full spatial freedom (6 d.o.f.). The general approach used in this paper could also be applied to the analysis and, in particular, to the design of other rigs used for biomechanical testing of post-mortem human joint specimens.